Diabetic Peripheral Neuropathy Affects Pinch Strength and Hand Dexterity in Elderly Patients - Qi Zhang; Yifang Lin; Xinhua Liu; Li Zhang; Yan Zhang; Dong Zhao; Qi Lu; Jie Jia (Neural Plasticity)
Objective. Diabetic peripheral neuropathy (DPN) is one of the most common chronic complications of diabetes, leading to disability and decreased quality of life. In past research and clinical studies, the lower limb function of DPN patients was often the principal subject of research, with little attention given to the upper limb and hand. Our goal was to assess and compare hand function between elderly diabetic patients with DPN and without DPN. Methods. A total of 52 diabetic patients were registered and underwent hand function assessments and electrodiagnostic tests. Dynamometer, pinch meter, Semmes Weinstein monofilaments, and the Purdue Pegboard Test (PPT) were used to assess the patients’ grip strength, pinch strength, tactile sensory threshold, and hand dexterity. Results. Compared with the non-DPN group, the elderly DPN group showed worse thumb-middle fingertip pinch strength and thumb-little fingertip pinch strength in the dominant hand (3.50 (2.50, 4.25) vs. 4.50 (3.00, 5.00), p=0.019; 1.50 (1.00, 2.00) vs. 2.50 (2.00, 3.00), p<0.001); the elderly DPN group displayed worse thumb-middle fingertip pinch strength, thumb-ring fingertip pinch strength, and thumb-little fingertip pinch strength in the nondominant hand (3.50 (2.00, 4.50) vs. 4.00 (3.00, 5.00), p=0.013; 2.50 (1.25, 3.00) vs. 3.00 (2.50, 3.50), p=0.033; 1.00 (0.75, 2.25) vs. 2.50 (2.00, 2.50), p<0.001). The elderly DPN group scored lower than the non-DPN group on the PPT test of assembly (13.96±5.18 vs. 16.96±4.61, t=2.212, p=0.032). Conclusion. Motor function limitation is the principal hand dysfunction in elderly patients with DPN, which is mainly manifested as a decline in fingertip pinch strength and a decrease in hand dexterity. This trial is registered with Clinical Trial Registry no. ChiCTR1900025358.